(untitled) (International Journal of Scientific Trends, 2026)
This article is devoted to the comparative-legal analysis of the legal mechanisms for applying mediation in the enforcement stage of judicial acts in the legal systems of foreign states — the European Union, Germany, France, the United Kingdom, the United States, Singapore, and Japan — on the basis of comparative-legal methodology. The concept of ’post-judgment mediation’, the institutions for reaching agreement in enforcement proceedings, and the empirical impact of mediation on enforcement effectiveness are studied in detail. The article concludes with a theoretical model summarising foreign experience and practical recommendations.